The effect of financial inclusion on multidimensional poverty: the case of Vietnam - Huong Thi Thanh Tran; Ha Thi Thu Le; Nga Thanh Nguyen; Tue Thi Minh Pham; Huyen Thanh Hoang (Cogent Economics & Finance, 2022)
Poverty reduction has become a top goal in the socio-economic development strategies of countries and a topic of interest for researchers. A number of prior empirical studies have identified the importance of financial inclusion to poverty reduction. However, most of these studies assess the effect of financial inclusion on income poverty reduction. There are relatively few studies evaluating the impact of financial inclusion, especially in terms of household use of financial products and services, on multidimensional poverty reduction. This study uses a multivariate probit model with a dataset from Vietnam to estimate the effect of financial inclusion in terms of household use of financial products and services and other factors on multidimensional poverty. The results show that financial inclusion reduces multidimensional poverty. Specifically, households owning bank accounts, having savings at banks, using debit cards, credit cards, or investing in stocks or bonds are less likely to fall into multidimensional poverty. Based on the findings, we provide several recommendations for policymakers to increase the level of households' use of financial products and services.
Keywords: 330; financial inclusion; multidimensional poverty; multivariate probit; poverty reduction